Driving is believing: Using telepresence robots to access makerspace for teachers in rural areas. (30th April 2022) - Chen, Ye; Cao, Li; Guo, Lin; Cheng, Jiaming
Abstract: This study explored two different ways for K‐12 school teachers to access educational makerspace through virtual fieldtrips. K‐12 school teachers from rural areas of the Southeast USA were divided into two groups. The experimental group ( n = 48) drove telepresence robots to take their fieldtrip, while the comparison group ( n = 23) watched the same fieldtrip through a recorded video. Analyses of the quantitative and qualitative data, collected through surveys and written reflections, showed that the experimental group reported significantly higher scores in embodiment, social presence and engagement (ie, behaviour, emotion and cognition) than the comparison group, and that actual driving the robots for the virtual fieldtrips was highlighted as a favored experience. Educational significance and implications are discussed. Practitioner notes What is currently known about this topic With makerspaces gaining increasing attention in K‐12 education, professional development (PD) opportunities are needed to help teachers understand makerspaces and related technologies. Teachers in rural areas are faced with the challenges of accessing makerspace resources and opportunities, especially during the COVID‐19 pandemic. Little research has explored teacher makerspace PD in rural areas. Maker resource deficiency in rural areas and the COVID‐19 pandemic call for an alternative approach to the makerspace PD, particularly for teachers in rural areas. What this paper adds Explored the use of telepresence robots for rural teachers to access an authentic makerspace through virtual fieldtrips. Examined the effects of virtual fieldtrip to access makerspaces on K‐12 teachers' embodiment, social presence and engagement. Examined the aspects of the telepresence fieldtrip that were most valuable to K‐12 teachers. Investigated the factors that contribute to teachers' engagement in a virtual fieldtrip. Implications for practitioners Telepresence robot was an effective tool that enabled teachers in rural areas to explore authentic makerspaces through a virtual trip over distance. To help teachers conceptualize the idea of makerspace, it is important to allow teachers to move in the physical makerspace and interact with the environment. To design an engaging fieldtrip that triggers active learning, more attention should be given to how to develop the emotional aspect of a fieldtrip experience. Embodiment plays an important role in virtual fieldtrips. When teachers have a higher level of embodiment, they are more likely to be emotionally and cognitively engaged in a fieldtrip experience.